Traditional Food-Making In Story Photography: Emping Melinjo By Bu Sum, Kartasura - Iman, Priaji; Khasanah, Azizah Uswatun (Institut Seni Indoensia Surakarta, 2025)
The creative research entitled “Traditional Food Production in Story Photography: Emping Melinjo by Bu Sum, Kartasura” aims to visualize the traditional production process of emping melinjo so that it can be better understood and appreciated by society, especially the younger generation. Through a narrative photography approach, this work serves as both an educational medium and an effort to preserve cultural values and local wisdom. The object of this work covers the entire process of emping melinjo production, which is still carried out manually using human labor. The creation method includes data collection, exploration, experimentation, production, editing, and presentation. The final work consists of 18 main photographs in 24R size (60 × 90 cm) and 9 supporting photographs in 10RL size (20 × 30 cm). This work is expected to broaden appreciation of the traditional emping melinjo-making process and foster a deeper understanding among younger generations of the cultural values contained within.